POLICIES OF ECONOMIC GROWTH IN BRAZIL AND THE SPATIAL DISTRIBUTION OF PRODUCTION (Revista de Estudos Sociais, 2021)
The Brazilian economic growth occurred in concentrated form in the Southeast and South. From 1950 it was undertaken some structural character of measures, targeting regional economic development with spatial distribution of economic growth. Some restructuring and promotion programs of reducing regional disparities were implemented with little or no success. Thus, the purpose of this article is to study the spatial distribution of production in Brazil in three sectors, namely industry, services and agriculture, among the five major regions: North, Northeast, Southeast, South and Midwest, from 1950-2009, using as variable the Gross Domestic Product - GDP. The empirical methodology is to construct indexes of location and specialization, from 2014 IPEADATA data. The results show a tendency to deconcentration of productive activities, with reduced participation of the Southeast. However, there is still strong concentration of production in this region, with only a slight tendency to increase production in other regions of the country. In fact, it is not known if there is devolution or sprawling growth, related to the spatial distribution of investment in other areas of the country.